Combination therapy of GnRHa, RhGH and anastrozole to improve final adult height deficit in CAH children with CPP - Xiaoxiao Liu; Fei Liu; Yingyi Qi; Xinyi Han; Shifeng Ma; Rongxiu Zheng (BMC Pediatrics)
Abstract Background To investigate the clinical and genetic characteristics of classic congenital adrenal hyperplasia (CAH) patients. To determine whether gonadotropin-releasing hormone analogs (GnRHa) + recombinant human growth hormone (rhGH) + Anastrozole combined therapy improves the final adult height of CAH patients with central precocious puberty (CPP). Methods We described the clinical and genetic characteristics of 16 classic CAH patients, and performed pathogenic analysis and structural modeling of the newly discovered mutation. By using the method of self-before and after control, we statistically analyzed bone age advancement, predicted adult height (PAH) and other indicators of 7 CAH children with CPP before and after combined treatment to observe its effect on adult height. Results All patients showed high levels of 17-hydroxyprogesterone, testosterone and adrenocorticotropic hormone. All patients had CYP21A2 gene mutations, and the newly discovered mutation c.79 A > G (p.Ser27Gly) may change the hydrophilicity of the protein and affect its function. Seven CAH patients with CPP were diagnosed at 5.6 (3.5 to 7.3) years. Their target height was 0.18 (-1.2 to 0.78) SD, and the PAH at the start of treatment was − 3.01 (-3.75 to -2.89) SD. The ages at which CAH patients with CPP started to be treated with GnRHa, rhGH and Anastrozole were 5.8 (5.5 to 8.7), 7.1 (5.5 to 9.8), 8.7 (7.6 to 10.7) years old, and discontinued them at 8.8 (7.5 to 10.2), 10.4 (9.0 to 12.7), 11.0 (9.7 to 12.7) years old, respectively. The PAH at treatment end was − 0.28 (-1.2 to 0.4) SD. The final height was − 0.28 (-1 to 1.04) SD, significantly higher than the initial PAH (P < 0.001) and similar to the target height (P = 0.478). Conclusion GnRHa + rhGH + Anastrozole therapy can improve the final adult height of CAH patients with CPP. In addition, this study also discovered a new CYP21A2 gene mutation c.79 A > G.